A Pragmatic Approach: Politeness Strategies Used by Dylan Pross vs Miawaug during battle FF - Yustina Fitriani; Murti Bandung (LPPM Universitas Bumigora Mataram, 2022)
Youtube is a video sharing service that can be accessed freely by many people. They tried to show their skill from its channel, especially gamers. Dylan Pros and Miawaug are the gamers who are interested in playing Free Fire (FF). During the battle, their utterances delivered in many ways. The aim of this research is to know the politeness strategy used by Dylan Pros and Miawaug during battle FF. This research is categorized as a descriptive qualitative with a pragmatic approach. The theory of politeness strategy by Brown and Levinson are categorized into four strategies. They are Bald-on Record Strategy, Positive Politeness Strategy, Negative Politeness Strategy, and Off-record Strategy. The data were taken from the utterances of Dylan Pros and Miawaug. The results showed that the utterances found in Bald-on Record strategy was 87 utterances, Positive Politeness strategy was 32 utterances, Negative Politeness strategy was 15 utterances, and Off-record strategy was 2 utterances. The conclusion of this research is that Bald-on Record strategy was more dominant in its use than others.